Masyarakat Madani dan Relevansinya Dengan Pendidikan Islam (Telaah Filosofis) - Nasution, Hambali Alman; Trisandi, Trisandi (STAI Serdang Lubuk Pakam, 2020)
This study aims to analyze the concept of civil society and its relevance to Islamic education from a philosophical perspective. This study uses a qualitative research method based on library research (library research). The main data sources in this research are Al-Qur'an and Hadith, which are interpreted from a philosophical point of view. Meanwhile, the supporting data sources are related books and journals. The results of this study explain that civil society is a group of individuals or groups who carry the vision and mission to achieve the desired life goals, where they influence each other and are bound based on divine law, namely the Al-Qur'an. and Al-Hadith to achieve the goals of life so that the function of education in civil society is as a means to achieve a life that is prosperous, just, prosperous and in accordance with the desired ideals as well as improving, controlling and leading to the right path, developing potential, and shaping character which is in accordance with Islamic teachings. This concept certainly has relevance to Islamic education, where Islamic education is broadly oriented not only to individual development but also to the formation of a civil society.